SPOTIFY APPLICATION ON THE STUDENTS’ VOCABULARY ACHIEVEMENT: AN EXPERIMENTAL STUDY - Permani, Debina Putri; Rahayu, Endang Mastuti; Agustina, Eliasanti (Jurnal Pendidikan Bahasa Inggris Proficiency, 2025)
The study investigated the influence of the Spotify application on the vocabulary achievement of eleventh-grade students. The research identified the need for engaging methods to enhance vocabulary learning, as non-technology media approaches often failed to captivate students. Spotify’s audio media features, such as songs and lyrics, offered contextual and interactive learning opportunities. Previous studies and the theoretical framework suggested that digital platforms like Spotify could significantly influence students’ vocabulary acquisition by presenting language in dynamic and authentic contexts. This study took a quantitative approach, using a pretest and posttest experimental research design that involved 80 students divided into experimental and control groups. The experimental group used Spotify for vocabulary exercises, including listening to curated songs, analyzing lyrics, and completing interactive tasks, while the control group received conventional lessons. Data analysis through IBM SPSS 19 assessed vocabulary improvements between the two groups, highlighting Spotify’s pedagogical advantages in creating engaging and effective language-learning environments. The results confirmed the alternative hypothesis (Hₐ), indicating that Spotify enhanced vocabulary achievement. The null hypothesis (H₀), which assumed no significant difference, was rejected. The results confirmed that Spotify enhanced vocabulary achievement. This suggested that integrating Spotify into language instruction not only influenced vocabulary retention but also fostered motivation and engagement among students, marking it as an effective educational tool.